2015
DOI: 10.1007/s10545-015-9866-0
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant immune‐related events in Wilson disease: implications for monitoring chelator therapy

Abstract: Under long-term d-penicillamine therapy a minority of patients developed immune-mediated disease. Elevations in antinuclear antibodies were found frequently, but no correlations were evident between increases in antinuclear antibodies and the development of immune-mediated diseases or medical regimes. Thus, the value of antinuclear antibodies for monitoring adverse events under chelator therapy seems to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…One study found more patients treated with DPen (6/91, 6%) to develop autoimmune diseases as compared to Zn (0/58) or trientine (0/58) . One study detected no difference between DPen‐ and Zn‐treated patients for the 15‐years probability of survival (78 ± 6% vs 67 ± 17%) .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…One study found more patients treated with DPen (6/91, 6%) to develop autoimmune diseases as compared to Zn (0/58) or trientine (0/58) . One study detected no difference between DPen‐ and Zn‐treated patients for the 15‐years probability of survival (78 ± 6% vs 67 ± 17%) .…”
Section: Resultssupporting
confidence: 77%
“…A total of 174 records were selected for full‐text screening to assess eligibility. Of these, 26 publications reporting on 23 studies met our inclusion criteria (Figure ) . Reasons for exclusion of the 148 studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, elevated serum antinuclear antibodies did not help predict longterm penicillamine associated immunological reactions. 67 Overall, most of the penicillamine-induced immunological adverse effects can be managed by concomitant steroids. 43,46 On prolonged penicillamine use, patients may also develop various skin lesions related to interference of penicillamine with collagen and elastin linking.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…In a study, elevated serum antinuclear antibodies did not help predict long-term penicillamine associated immunological reactions. 67 Overall, most of the penicillamine-induced immunological adverse effects can be managed by concomitant steroids. 43 , 46 On prolonged penicillamine use, patients may also develop various skin lesions related to interference of penicillamine with collagen and elastin linking.…”
Section: Resultsmentioning
confidence: 99%